LncRNA NBR2 aggravates hepatoblastoma cell malignancy and promotes cell proliferation under glucose starvation through the miR-22/TCF7 axis. Issue 5 (19th March 2021) - Zhu, Chengguang; He, Xiangling; Chen, Keke; Huang, Zhijun; Yao, Anqi; Tian, Xin; You, Yalan; Zeng, Minhui
ABSTRACT: Hepatoblastoma (HB) is the most commonly seen pediatric liver malignancy. With frequent mutations in CTNNB1 gene that encodes β‐catenin, hepatoblastoma has been considered as a Wnt/β‐catenin‐activated malignant tumor. Altered glucose metabolism upon nutrient deprivation (glucose starvation) might also be a critical event in hepatoblastoma carcinogenesis. The present study provides a lncRNA NBR2/miR-22/TCF7 axis modulating proliferation, invasion, migration, and apoptosis of hepatoblastoma cells upon glucose starvation through Wnt and downstream TCF7 signaling pathways. The expression of NBR2 is significantly increased within hepatoblastoma tissue samples; moreover, under incubation with 0 mM glucose (glucose starvation), NBR2 expression is significantly upregulated. NBR2 silencing not only inhibited hepatoblastoma cell viability, invasion, and migration under normal culture condition but also promoted the cell apoptosis under glucose starvation. NBR2 silencing in hepatoblastoma cells also decreased TCF7 mRNA expression and TCF7 protein levels, as well as the protein levels of the cell cycle, glucose entrapment, and EMT markers. miR-22 is directly bound to both NBR2 and TCF7; lncRNA NBR2 counteracted miR-22-mediated repression on TCF7 via acting as a ceRNA. The effects of NBR2 silencing on TCF7 expression, hepatoblastoma cell phenotype, and cell cycle, glucose entrapment, and EMT markers were all significantly reversed by miR-22 inhibition. In conclusion, lncRNA NBR2 aggravates hepatoblastoma cell malignancy through competing with TCF7 for miR-22 binding, therefore counteracting miR-22-mediated repression on TCF7. LncRNA NBR2 might be a promising target to inhibit hepatoblastoma cell proliferation under glucose starvation.